TINGKAT ADOPSI INOVASI BIOSECURITY AYAM RAS PETELUR DI KABUPATEN SIDRAP DAN FAKTORFAKTOR YANG MEMPENGARUHI - Rusni Rusni (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2015)
In order to encourage the adoption of innovations biosecurity atlayer farmers, it requires an understanding of innovation adoptionbiosecurity layer and its influencing factors. This research aims to determineadoption of innovation level of biosecurity layer and its influencing factors.The Method is biosecurity weighting which consists of layer sourcesbiosecurity, disrupt animal biosecurity, guests and workers biosecurity, sickanimal biosecurity, feed biosecurity, waste biosecurity and egg cratesbiosecurity, while the adoption innovation influencing factors use infrensialstatistics with test F and t test. The Results show the innovation adoptionlevel of biosecurity layer are low in Sidrap on disrupt animal biosecurity asmany as 59 people or 67.82%, guests and workers biosecurity consists of 59people or 67.82%, while for the factors that influence the level of adoption ofinnovation is scale effort and behavior control. The conclusion is There aretwo factors that affect the level of adoption innovation layer in Sidrap, Thefirst is The Enhancement of adoption innovation biosecurity can be startedon a larger scale and the second is The ability to control his behavior.